Nico Stehr: Pioneer in the Theory of Society and Knowledge (Pioneers in Arts, Humanities, Science, Engineering, Practice,, 2018)
This unique volume brings together a selection of the most important texts of Nico Stehr for the first time and puts them in dialogue with original research that draws on his prolific work. Covering five decades of pioneering sociological research on the theory of society and knowledge, the book introduces the reader to Stehr's seminal inquiries into the economic, political and social role of knowledge. Original concepts, such as his groundbreaking studies on the Knowledge Society, are introduced as the volume traces Stehr's pursuit of social scientific research as a source of practical knowledge for modern society. The book comprises three parts devoted to the many facets and the remarkable range of Nico Stehr's oeuvre. Part 1 provides an introduction to the significance of his pioneering work and career. Part 2 demonstrates the practical application of Nico Stehr's research as seen through the eyes of eminent scholars. Part 3 presents a selection of the milestones of his publications.